2018
DOI: 10.1111/cdev.13166
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Precursors of Relational Aggression From Late Childhood Through Adolescence

Abstract: Relational aggression—a psychological form of aggression—has numerous negative consequences for physical and emotional health. However, little is known about the risk factors that lead youth to engage in relational aggression. Using multimethod data from a longitudinal research of 674 Mexican‐origin youth, this study examined the influence of parents, siblings, and peers on the development of relational aggression. Increases in relational aggression from age 10 to 16 were associated with: (a) low levels of par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In the externalizing domain, studies have found that high-school-aged youth born in Mexico (vs. the United States) have lower rates of substance use (Prado et al, 2009;Vaughan et al, 2016), which may be reflected in the development of conscientiousness. However, other studies suggest that nativity does not affect development within these domains (e.g., see Aizpitarte et al, 2019;Gonzales et al, 2017). Given the conceptual overlap between Big Five personality traits and internalizing/externalizing mental health constructs that are potentially impacted by nativity, it would be informative to test whether nativity moderates personality trait development in Mexican-origin youth from adolescence to early adulthood.…”
Section: Generalizability Versus Culture-specificity Of Personality T...mentioning
confidence: 99%
“…In the externalizing domain, studies have found that high-school-aged youth born in Mexico (vs. the United States) have lower rates of substance use (Prado et al, 2009;Vaughan et al, 2016), which may be reflected in the development of conscientiousness. However, other studies suggest that nativity does not affect development within these domains (e.g., see Aizpitarte et al, 2019;Gonzales et al, 2017). Given the conceptual overlap between Big Five personality traits and internalizing/externalizing mental health constructs that are potentially impacted by nativity, it would be informative to test whether nativity moderates personality trait development in Mexican-origin youth from adolescence to early adulthood.…”
Section: Generalizability Versus Culture-specificity Of Personality T...mentioning
confidence: 99%
“…Examples of relational aggression include, intentionally ignoring or excluding an individual from an activity or group interaction, spreading malicious rumours, and defamatory gossip (Crick & Grotpeter, 1995;Goldstein, 2011;Murray-Close et al, 2010). Relational aggression has been associated with a host of internalizing and externalizing problems, which include antisocial behaviour, drug and alcohol abuse, Attention-Deficit/Hyperactivity Disorder (ADHD), depression, anxiety, physical aggression, impaired prosocial behaviour, as well as antisocial and narcissistic personality traits (Aizpitarte, Atherton, Zheng, Alonso-1 The University of Edinburgh, School of Health in Social Science, Medical School (Doorway 6), Room 3.06A, Teviot Place, Edinburgh, EH8 9AG Corresponding author: Panagiota Ira Bitsola (ira.bitsola@yahoo.com) Arbiol, & Robins, 2018;Crick & Grotpeter, 1995;Keenan, Coyne, & Lahey, 2008;Linder et al, 2002;Marsee, Silverthorn, & Frick, 2005;Ostrov, Kamper-DeMarco, Blakely-McClure, Perry, & Mutignani, 2019;Sullivan, Farrell & Kliewer, 2006).…”
Section: Relational Aggressionmentioning
confidence: 99%
“…It would be ideal if romantic relational aggression could be stopped before escalating into other forms of aggression (e.g., physical). The majority of studies assessing relational aggression were conducted with school-aged children (Aizpitarte et al, 2018;Crick & Grotpeter, 1995;Ostrov et al, 2019;Prinstein, Boergers, & Vernberg, 2001). However, little is known about whether these variables have utility in understanding relational aggression among young adults in their romantic relationships, as it appears to be an understudied population.…”
Section: The Current Studymentioning
confidence: 99%
“…Research on relational aggression during early childhood suggests that these behaviors often take on direct forms, being clearly visible to the victim, bystanders, and adult observers, and are rooted in the immediate situational context (for example, statements like "I won't be your friend anymore unless you give me that toy," "You can't come to my house because you are mean," along with actions like covering ears to signal ignoring; [29]. Relational aggression has been linked to an array of internalizing and externalizing problems, including antisocial behavior, substance abuse, attentiondeficit/hyperactivity disorder (ADHD), depression, anxiety, physical aggression, impaired prosocial behavior, as well as traits associated with antisocial and narcissistic personalities [30]- [32].…”
Section: Introductionmentioning
confidence: 99%